TOSREC-FR : Normalisation franco-québécoise du Test of Silent Reading Efficiency and Comprehension pour la sixième année - Renauld, Stéphanie; Guay, Frédéric; St-Pierre, Marie-Catherine (Canadian Journal of Education/Revue canadienne de l’éducation, 2021)
This study presents the results of the standardization of the Test of Silent Reading Efficiency and Comprehension (TOSREC) among French sixth graders from Quebec and the results of the TOSREC-FR validation process. The TOSREC-FR for Grade 6 is a screening tool that can be administered in three minutes to an entire class to assess students' reading comprehension skills. The TOSREC-FR for grade 6 was standardized in thirteen classes (from 77 to 249 students per questionnaire) in the province of Quebec during the 2018-2019 and 2019-2020 school years. The standardization of TOSREC-FR allows students to be classified according to their reading level and to identify students at risk of presenting academic difficulties before entering secondary school.